1995
DOI: 10.1080/00029157.1995.10403158
|View full text |Cite
|
Sign up to set email alerts
|

Client-Centered Hypnotherapy for Tinnitus: Who is Likely to Benefit?

Abstract: In this study we prospectively analyzed 41 patients, 15 females and 26 males with a mean age of 54, who underwent three sessions of client-centered hypnotherapy for their tinnitus. Of these patients, 28 (68%) showed some benefit for their tinnitus 3 months after completing their hypnosis, and 13 (32%) showed no evidence of improvement for their tinnitus. Hearing loss was associated with a nonbeneficial outcome for tinnitus treated with hypnotherapy. Of the nonbeneficial group, 46% had a hearing loss of 30 db o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…One study found hypnosis to be no better than counseling, and one study found that the nonresponders to hypnotherapy were the patients with the worst hearing losses. 47–50 …”
Section: Discussionmentioning
confidence: 99%
“…One study found hypnosis to be no better than counseling, and one study found that the nonresponders to hypnotherapy were the patients with the worst hearing losses. 47–50 …”
Section: Discussionmentioning
confidence: 99%
“…Psychological counseling still remains an option for patients who are unable to reduce anxiety due to tinnitus [24]. Elaboration of these techniques includes biofeedback [6], hypnotherapy [20] and even yoga [18]. In all of these strategies patients have demonstrated definite benefit, but without elimination of tinnitus.…”
Section: Medical Therapiesmentioning
confidence: 99%